Pedagogical strategies to cater for dyslexic learners in the EFL classroom - Núñez Soto, Rafael (2021)
This essay seeks to help teachers reflect on the importance of catering for dyslexic individuals in the EFL classroom. For this purpose, a general review of the causes and manifestations of dyslexia will be presented, so that teachers can identify students that might have different learning needs. The discussion centers on the necessity of enforcing pedagogical tools that might serve dyslexic students. Hence, aspects such as using modern technology as an ally, providing individualized learning experiences, adapting material, and praising and motivating students will be analyzed. Besides the need to create an inclusive learning environment where students, teachers, relatives, and stockholders become aware of the needs of dyslexic individuals will be addressed. A final consideration of how teachers can offer additional support to dyslexic learners will be discussed.